Knockdown of Annexin A2 Enhances Radiosensitivity by Increasing G2/M-Phase Arrest, Apoptosis and Activating the p38 MAPK-HSP27 Pathway in Nasopharyngeal Carcinoma - He, Huocong; Lin, Keyu; Zou, Changyan; Pan, Jianru; Fu, Wankai; Zhou, Yan; Lin, Huamei; Chen, Chao; Su, Ying (Frontiers in Oncology, 2022)
Annexin A2 (ANXA2) has been found to be involved in cancer proliferation, metastasis and prognosis; however, its exact role in nasopharyngeal carcinoma (NPC) radioresistance remains unknown. We found that ANXA2 expression was correlated with prognosis in NPC patients, and longer overall survival in NPC patients with low ANXA2 expression than those with high ANXA2 expression. ANXA2 knockdown increased the radiosensitivity in radioresistant NPC cells, and ANXA2 overexpression decreased the radiosensitivity in NPC cells. Knocking-down ANXA2 expression increased the irradiation-induced apoptosis of radioresistant NPC cells, and ANXA2 overexpression decreased the irradiation-induced apoptosis of NPC cells. ANXA2 knockdown induced G2/M phase arrest in NPC cells post-irradiation, and ANXA2 overexpression abrogated G2/M phase arrest in NPC cells post-irradiation. ANXA2 overexpression resulted in inhibition of the p38 MAPK-HSP27 pathway, while ANXA2 knockdown resulted in activation of the p38 MAPK-HSP27 pathway. In addition, ANXA2 knockdown increased the radiosensitivity of the xenografted tumors in nude mice. Our data demonstrate that Knockdown of Annexin A2 enhanced radiosensitivity in NPC by increasing G2/M-phase arrest, apoptosis and activating the p38 MAPK-HSP27 pathway. ANXA2 may be a promising target used to overcome radioresistance in NPC.